2023
DOI: 10.3390/w15111977
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dissolved Oxygen on the Performance and Microbial Dynamics in Side-Stream Activated Sludge Hydrolysis Process

Abstract: Dissolved oxygen (DO) plays an important role in the performance of biological wastewater treatment systems. This study investigated the effect of the DO concentration on nutrient removal performance and microbial community structure in side-stream activated sludge hydrolysis (SSH) and conventional anaerobic/anoxic/aerobic (A2O) processes. The results showed that the change in DO had little effect on the removal performance of chemical oxygen demand (COD), and the removal efficiencies were about 90% for both r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…In the form of nutrients and gases, oxygen generated under anaerobic conditions broke down chemical molecules into simpler variants. DO played a crucial role in reducing the contamination load on natural water and in aerobic treatment, which cleaned domestic and industrial wastewater due to the oxidation and reduction process [22]. Table 2 shows that water experienced a decrease in dissolved oxygen concentration after 30 days of phytoremediation.…”
Section: Tempe Physicochemical Characteristicsmentioning
confidence: 99%
“…In the form of nutrients and gases, oxygen generated under anaerobic conditions broke down chemical molecules into simpler variants. DO played a crucial role in reducing the contamination load on natural water and in aerobic treatment, which cleaned domestic and industrial wastewater due to the oxidation and reduction process [22]. Table 2 shows that water experienced a decrease in dissolved oxygen concentration after 30 days of phytoremediation.…”
Section: Tempe Physicochemical Characteristicsmentioning
confidence: 99%
“…Notably, the relative abundance of potential PAO (i.e., Acinetobacter) increased from 0.08% to 5.81-12.57% with the addition of PLA MPs. Although Acinetobacter's contribution to EBPR remains controversial, many studies have shown that Acinetobacter has the ability to accumulate polyP and PHA [66][67][68], and it has previously been proposed to behave as PAOs in EBPR systems [69,70]. The relative abundance of Competibacter increased from 0.05% in R0 to 0.16% in R1, but decreased to 0.03% in R3 as PLA MPs concentration continued to increase.…”
Section: Functionally Relevant Microbial Populationsmentioning
confidence: 99%